Functional abdominal pain and irritable bowel syndrome in children and adolescents. Issue 3 (May 2011) - Chiou, Eric; Nurko, Samuel
Functional abdominal pain (FAP) and irritable bowel syndrome (IBS) are both associated with recurrent abdominal pain and are among the most commonly diagnosed medical problems in pediatrics. The majority of patients with mild complaints improve with reassurance and time. For a distinct subset of patients with more severe and disabling illness, finding effective treatment for these disorders remains a challenge. Based on the biopsychosocial model of functional disease, the Rome III criteria have helped frame FAP and IBS in terms of being a positive diagnosis and not a diagnosis of exclusion. However, the lack of a single, proven intervention highlights the complex interplay of pathologic mechanisms likely involved in the development of childhood FAP and IBS and the need for a multidisciplinary, integrated approach. This article discusses the epidemiology, proposed mechanisms, clinical approach and therapeutic options for the management of FAP and IBS in children and adolescents.